The quiet revolution the struggle for the rights of disabled Americans - Haskins, James 1941-2005; Stifle, J. M. (Thomas Y. Crowell, 1979)
Focuses on the human and civil rights the handicapped are campaigning for, and on the various methods they are using to bring change to society and make it more aware of the needs of the disabled.